Fe-mof / cnt electromagnetic shielding film based on pbo nanofiber and preparation method thereof
Patent Information
- Application Number
- CN202611331386.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]本发明的目的在于提供PBO纳米纤维基Fe-MOF/CNT电磁屏蔽薄膜的制备方法,解决了现有Janus型电磁屏蔽材料中异质界面结合不足、电磁损耗机制单一的问题
(1)本发明采用PBO纳米纤维作为复合薄膜的基体材料,PBO纳米纤维具有较高的力学强度、耐热性和化学稳定性,能够为复合薄膜提供良好的力学支撑;同时,PBO纳米纤维网络有利于功能填料的负载和固定,提高复合薄膜的结构稳定性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic shielding material preparation technology, specifically relating to a method for preparing PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding films, and further relating to PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding films. Background Technology
[0002] Existing electromagnetic shielding materials typically rely on conductive networks to reflect electromagnetic waves and achieve energy attenuation through mechanisms such as dielectric loss and magnetic loss within the material. While single-conductive shielding materials possess high electromagnetic wave reflection capabilities, a significant amount of electromagnetic waves is reflected back into the environment, easily leading to secondary electromagnetic pollution. Materials that rely solely on absorption losses often fail to achieve high shielding effectiveness. Therefore, constructing composite structures with different electromagnetic response functional regions, allowing incident electromagnetic waves to undergo multiple loss processes within the material, is an important approach to improving electromagnetic shielding performance.
[0003] Polymer-based electromagnetic shielding materials, due to their low density, good processing adaptability, and excellent corrosion resistance, are gradually becoming an important research direction to replace traditional metal-based shielding materials. Among them, composite films with asymmetric functional distributions provide a new design approach for optimizing electromagnetic shielding performance. This structure effectively separates the conductive and magnetic loss regions by introducing different functional components on both sides of the material, thereby promoting multiple attenuation of electromagnetic waves. However, since different types of functional fillers are usually used on both sides of this structure, there are significant compositional differences between the functional layers, which can easily lead to problems such as discontinuous heterogeneous interfaces, insufficient interfacial compatibility, and reduced interlayer bonding strength. Especially in the process of assembling asymmetric structures layer by layer, the different functional layers are mainly bonded through interfacial contact. Without effective interface control strategies, problems such as interface defects and insufficient interlayer bonding can easily occur, thus affecting the mechanical stability and long-term performance of the material.
[0004] Poly(p-phenylene-2,6-benzoxazole) nanofibers (PBO) possess high aspect ratio, high strength, and excellent thermal stability. The fiber network they construct not only provides good mechanical support but also enhances the structural stability of composite films through interfacial interactions between heteroatoms in the benzoxazole structure and functional fillers. Carbon nanotubes (CNTs) exhibit excellent conductivity, flexibility, and chemical stability, effectively constructing conductive networks and enhancing electromagnetic wave conduction and dielectric loss capabilities. Iron-based metal-organic frameworks (Fe-MOFs) possess abundant pore structures, large specific surface areas, and tunable electromagnetic response characteristics. Their iron-based active centers can provide a certain magnetic response capability, and combined with interfacial polarization, dielectric loss, and magnetic loss mechanisms, they enhance the material's absorption and attenuation capabilities for electromagnetic waves. Therefore, by using PBO nanofibers as the common matrix for the two functional layers, and by assembling PBO / Fe-MOF absorption loss layer and PBO / CNT conductive loss layer layer by layer, the structural stability can be improved and the conductive loss-magnetic loss can be synergistically regulated, while maintaining the functional partitioning characteristics of the Janus structure. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding films, which solves the problems of insufficient heterogeneous interface bonding and a single electromagnetic loss mechanism in existing Janus-type electromagnetic shielding materials.
[0006] Another object of the present invention is to provide a PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film.
[0007] The technical solution adopted in this invention is a PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film, comprising a PBO / Fe-MOF absorption loss layer and a PBO / CNT conductive loss layer. Both functional layers use PBO nanofibers as a common matrix and are constructed by layer-by-layer assembly to form a composite electromagnetic shielding film with an asymmetric Janus structure.
[0008] Another technical solution adopted in this invention is a method for preparing PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding films, specifically as follows: Step 1: Prepare PBO nanofiber dispersion; Step 2, prepare CNT dispersion; Step 3, prepare Fe-MOF; Step 4: The PBO nanofiber dispersion and Fe-MOF are ultrasonically mixed to obtain a PBO / Fe-MOF mixture; Step 5: The PBO nanofiber dispersion and the CNT dispersion are ultrasonically mixed to obtain a PBO / CNT mixture; Step 6: Using a layer-by-layer assembly method, the PBO / Fe-MOF mixture and the PBO / CNT mixture are vacuum filtered to form a film and then hot-pressed to obtain a PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film.
[0009] The invention is further characterized in that, In step 1, specifically: PBO nanofibers are added to a mixed acid solvent system composed of trifluoroacetic acid and methanesulfonic acid, stirred, and acid-assisted dissociation is carried out for 24-96 hours to form a PBO nanofiber dispersion; then deionized water is added for solvent replacement, and the PBO filter cake is redispersed and homogenized after vacuum filtration and washing with deionized water to obtain a PBO nanofiber dispersion with a concentration of 0.5-5 mg / mL.
[0010] In step 2, specifically: CNTs are mixed with sodium dodecylbenzenesulfonate and added to deionized water. The mixture is then subjected to ultrasonic treatment using an ultrasonic cell disruptor with an ultrasonic power of 300-600 W and an ultrasonic time of 1-2 h to obtain a CNT dispersion with a concentration of 1-5 mg / mL.
[0011] Step 3 specifically involves: Fe(NO3)3·9H2O and terephthalic acid ligands were added to a mixed solvent consisting of N,N-dimethylformamide, deionized water, and ethanol, and stirred to form a homogeneous solution. Triethylamine was then added as a ligand deprotonating agent, and the mixture was stirred continuously before being transferred to a reaction vessel for a solvothermal reaction. After the reaction was completed, the resulting precipitate was collected, washed with deionized water and ethanol, and finally dried to obtain Fe-MOF powder. The molar ratio of Fe(NO3)3·9H2O to terephthalic acid ligands was 0.1–5:0.1–5; the solvothermal reaction temperature was 100–200 °C, the solvothermal reaction time was 6–24 h, the drying temperature was 50–70 °C, and the drying time was 12–24 h.
[0012] In step 5, the volume ratio of PBO nanofiber dispersion to CNT dispersion is 5~50:0.5~20.
[0013] In step 6, the hot pressing temperature is 50~80℃ and the hot pressing time is 15~30 h.
[0014] The beneficial effects of this invention are: (1) In this invention, PBO nanofibers are used as the matrix material of the composite film. PBO nanofibers have high mechanical strength, heat resistance and chemical stability, which can provide good mechanical support for the composite film. At the same time, the PBO nanofiber network is conducive to the loading and fixation of functional fillers, and improves the structural stability of the composite film.
[0015] (2) The present invention uses a layer-by-layer assembly method to construct a Janus structure composite film composed of a PBO / Fe-MOF absorption layer and a PBO / CNT conductive layer, which can respectively exert the electromagnetic wave absorption effect of Fe-MOF and the electromagnetic wave loss effect of CNT conductive network. By adjusting the filler content in different functional layers, the electromagnetic shielding performance of the composite film can be controlled.
[0016] (3) In the material of the present invention, both sides of the functional layer are made of PBO nanofibers as the matrix, so that different functional layers have the same fiber skeleton, which is beneficial to improve the interlayer bonding stability. At the same time, the interfacial interaction between PBO nanofibers and Fe-MOF and CNT can promote the stable distribution of functional components in the fiber network, thereby improving the problem of insufficient interfacial bonding of different components in traditional Janus structure composite materials. Attached Figure Description
[0017] Figure 1a These are photographs of the PBO / Fe-MOF layer in the composite film prepared in Example 2; Figure 1b These are photographs of the PBO / CNT layer in the composite film prepared in Example 2. Figure 1c This is a flexibility test diagram of the composite film prepared in Example 2; Figure 2a This is a SEM image of the PBO / Fe-MOF layer in the composite film prepared in Example 2; Figure 2b This is an EDS-C elemental distribution diagram of the PBO / Fe-MOF layer in the composite film prepared in Example 2; Figure 2c This is an EDS-O elemental distribution diagram of the PBO / Fe-MOF layer in the composite film prepared in Example 2; Figure 2d This is an EDS-Fe elemental distribution diagram of the PBO / Fe-MOF layer in the composite film prepared in Example 2; Figure 3a This is a SEM image of the PBO / CNT layer in the composite film prepared in Example 2; Figure 3b This is an EDS-C elemental distribution diagram of the PBO / CNT layer in the composite film prepared in Example 2; Figure 3c This is the EDS-N elemental distribution diagram of the PBO / CNT layer in the composite film prepared in Example 2; Figure 3d This is an EDS-O elemental distribution diagram of the PBO / CNT layer in the composite film prepared in Example 2; Figure 4a This is a cross-sectional SEM image (I) of the composite film prepared in Example 2; Figure 4b This is a cross-sectional SEM image (II) of the composite film prepared in Example 2; Figure 4c This is a cross-sectional SEM image (III) of the composite film prepared in Example 2; Figure 4d This is a cross-sectional SEM image (IV) of the composite film prepared in Example 2; Figure 4e This is an EDS elemental distribution diagram of the composite film prepared in Example 2; Figure 4f This is a carbon element distribution diagram of the composite film prepared in Example 2; Figure 4g This is a nitrogen element distribution diagram of the composite film prepared in Example 2; Figure 4h This is a diagram showing the O element distribution of the composite film prepared in Example 2; Figure 4i This is a Fe elemental distribution diagram of the composite film prepared in Example 2; Figure 5 This is a diagram showing the total electromagnetic shielding effectiveness of the composite film prepared in Example 1; Figure 6 This is a diagram showing the total electromagnetic shielding effectiveness of the composite film prepared in Example 2; Figure 7 This is a diagram showing the total electromagnetic shielding effectiveness of the composite film prepared in Example 3; Figure 8 This is a diagram showing the overall electromagnetic shielding effectiveness of the composite thin film prepared in Comparative Example 1. Figure 9 This is a diagram showing the overall electromagnetic shielding effectiveness of the composite film prepared in Comparative Example 2; Figure 10 This is a comparison chart of the absorption shielding effectiveness, reflection shielding effectiveness, and total shielding effectiveness of the composite films in the examples and comparative examples. Detailed Implementation
[0018] The present invention will now be described in detail with reference to specific embodiments and accompanying drawings.
[0019] This invention relates to an asymmetric Janus-structured PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film, comprising a PBO / Fe-MOF absorption loss layer and a PBO / CNT conductive loss layer. Both functional layers use PBO nanofibers as a common matrix and are constructed layer-by-layer to form a composite electromagnetic shielding film with an asymmetric Janus structure. In the PBO / Fe-MOF absorption loss layer, the Fe-MOF functional component utilizes its porous structure, iron-based active centers, and electromagnetic response characteristics to enhance electromagnetic wave absorption and attenuation through the synergistic effects of interfacial polarization, dielectric loss, and magnetic loss. In the PBO / CNT conductive loss layer, CNTs construct a conductive network to enhance electromagnetic wave reflection and dielectric loss capabilities. Stable bonding between the two functional layers is achieved through the continuous network of PBO nanofibers and the interfacial interactions with the functional fillers, resulting in a composite film with both high-efficiency electromagnetic shielding performance and excellent mechanical properties. The PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film exhibits an electromagnetic shielding effectiveness ≥ 40 dB and a tensile strength ≥ 50 MPa in the X-band of 8.2–12.4 GHz.
[0020] The preparation method of the PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film of the present invention is carried out according to the following steps: Step 1, Preparation of PBO nanofiber dispersion: PBO nanofibers are added to a mixed acid solvent system composed of trifluoroacetic acid (TFA) and methanesulfonic acid (MSA), stirred, and acid-assisted dissociation is performed to dissociate the PBO fibers and form a PBO nanofiber dispersion; then deionized water is added for solvent replacement, and residual acidic solvent is removed by vacuum filtration and washing with deionized water. The obtained PBO filter cake is redispersed and homogenized to obtain a stable and uniform PBO nanofiber dispersion.
[0021] The dissociation process was carried out in a mixed acid solvent system composed of TFA and MSA. The mass ratio of PBO fiber to mixed acid solvent is 0.05~2g:1 mL; the volume ratio of TFA to MSA is 1~5:1~5; the acid-assisted dissociation time is 24~96h; and the concentration of PBO nanofiber dispersion is 0.5~5mg / mL. Step 2, Preparation of CNT dispersion: CNTs are mixed with the surfactant sodium dodecylbenzenesulfonate and added to deionized water. The mixture is then subjected to ultrasonic treatment using an ultrasonic cell disruptor at low temperature to obtain a uniform and stable CNT dispersion. The mass-to-volume ratio of CNT, sodium dodecylbenzenesulfonate, and deionized water is 0.1–0.5 g: 0.25–12.5 g: 50–250 mL, the ultrasonic power is 300–600 W, the ultrasonic time is 1–2 h, and the concentration of the CNT aqueous dispersion is 1–5 mg / mL. Step 3, Preparation of Fe-MOF: Iron salt (Fe(NO3)3·9H2O) and terephthalic acid ligand are added to a mixed solvent composed of N,N-dimethylformamide (DMF), deionized water and ethanol, and stirred thoroughly to form a homogeneous mixed solution; then triethylamine is added as a ligand deprotonating agent to promote the activation of terephthalic acid ligand and regulate the nucleation process of Fe-MOF crystals. After continuous stirring, the mixture is transferred to a reaction vessel for solvothermal reaction. After the reaction is completed, the precipitate is collected and repeatedly washed with deionized water and ethanol to remove unreacted substances and residual solvent. Finally, Fe-MOF powder is obtained after drying.
[0022] The molar ratio of Fe(NO3)3·9H2O to terephthalic acid ligand is 0.1~5:0.1~5; the solvothermal reaction temperature is 100~200℃, the solvothermal reaction time is 6~24h, the drying temperature is 50~70℃, and the drying time is 12~24h. Step 4: The PBO nanofiber dispersion and Fe-MOF powder are ultrasonically mixed to obtain a PBO / Fe-MOF mixture; The mass-to-volume ratio of Fe-MOF powder to PBO nanofiber dispersion is 5~40 mg: 5~50 mL; Step 5: The PBO nanofiber dispersion and the CNT dispersion are ultrasonically mixed to obtain a PBO / CNT mixture; The volume ratio of PBO nanofiber dispersion to CNT dispersion is 5~50:0.5~20; Step 6: Using a layer-by-layer assembly method, the PBO / Fe-MOF mixture obtained in Step 4 and the PBO / CNT mixture obtained in Step 5 are vacuum filtered to form a film. After drying and hot pressing, an asymmetric Janus structure PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film is obtained.
[0023] The hot pressing temperature is 50~80℃, and the hot pressing time is 15~30 h.
[0024] Example 1 The present invention discloses a method for preparing a PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film, comprising the following steps: S1. 0.1 g of PBO nanofibers were added to a mixed acid solvent system consisting of TFA and MSA (TFA to MSA volume ratio of 1:1), and the mixture was magnetically stirred at room temperature for 72 h for acid-assisted dissociation. Subsequently, deionized water was added for solvent replacement, and residual acidic solvent was removed by vacuum filtration and washing with deionized water. Finally, the obtained PBO filter cake was redispersed in deionized water, and after homogenization, a PBO nanofiber dispersion with a concentration of 1 mg / mL was obtained.
[0025] S2. Mix 0.1 g CNT, 0.25 g sodium dodecylbenzenesulfonate and 50 mL deionized water, and treat with ultrasound at 500 W for 1.5 h to obtain a CNT dispersion with a concentration of 2 mg / mL.
[0026] S3. Add 2 mmol Fe(NO3)3·9H2O and 2 mmol terephthalic acid to a mixed solvent consisting of 25 mL DMF, 2 mL deionized water, and 2 mL ethanol, and stir thoroughly until a homogeneous solution is formed. Then add 2 mL triethylamine, continue stirring, and transfer the resulting mixed solution to a reaction vessel. Perform a solvothermal reaction at 120 °C for 10 h. After the reaction is complete, collect the product, wash with deionized water and ethanol, and then dry at 60 °C for 24 h to obtain Fe-MOF powder.
[0027] S4. Mix 15 mL of PBO nanofiber dispersion and 20 mg of Fe-MOF and sonicate to obtain PBO / Fe-MOF mixture.
[0028] S5. Mix 15 mL of PBO nanofiber dispersion and 1 mL of CNT dispersion and ultrasonically disperse to obtain PBO / CNT mixture.
[0029] S6. Using a layer-by-layer assembly method, the PBO / Fe-MOF mixture obtained in S4 and the PBO / CNT mixture obtained in S5 are sequentially assembled and filtered to form a film. After hot pressing at 65℃ for 17 h, an asymmetric Janus structure PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film is obtained.
[0030] The film was tested and found to have an average electromagnetic shielding effectiveness of 28.61 dB in the X-band (8.2 ~ 12.4 GHz) and a tensile strength of 52.5 MPa.
[0031] Example 2 The present invention discloses a method for preparing a PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film, comprising the following steps: S1. 0.2 g of PBO nanofibers were added to a mixed acid solvent system consisting of TFA and MSA (TFA to MSA volume ratio of 1.5:1), and the mixture was magnetically stirred at room temperature for 96 h for acid-assisted dissociation. Subsequently, deionized water was added for solvent replacement, and residual acidic solvent was removed by vacuum filtration and washing with deionized water. Finally, the obtained PBO filter cake was redispersed in deionized water, and after homogenization, a PBO nanofiber dispersion with a concentration of 1 mg / mL was obtained.
[0032] S2. Mix 0.1 g CNT, 0.25 g sodium dodecylbenzenesulfonate and 50 mL deionized water, and treat with ultrasound at 400 W for 2 h to obtain a CNT dispersion with a concentration of 2 mg / mL.
[0033] S3. Add 2 mmol Fe(NO3)3·9H2O and 2 mmol terephthalic acid to a mixed solvent consisting of 25 mL DMF, 2 mL deionized water, and 2 mL ethanol, and stir thoroughly until a homogeneous solution is formed. Then add 2 mL triethylamine, continue stirring, and transfer the resulting mixed solution to a reaction vessel. Perform a solvothermal reaction at 150 °C for 8 h. After the reaction is complete, collect the product, wash with deionized water and ethanol, and then dry at 65 °C for 20 h to obtain Fe-MOF powder.
[0034] S4. Mix 15 mL of PBO nanofiber dispersion and 20 mg of Fe-MOF and sonicate to obtain PBO / Fe-MOF mixture.
[0035] S5. Mix 15 mL of PBO nanofiber dispersion and 3 mL of CNT dispersion and ultrasonically disperse to obtain PBO / CNT mixture.
[0036] S6. Using a layer-by-layer assembly method, the PBO / Fe-MOF mixture obtained in S4 and the PBO / CNT mixture obtained in S5 are sequentially assembled and filtered to form a film. After hot pressing at 60℃ for 24 h, a nano-PBO fiber-based Fe-MOF / CNT asymmetric Janus structure composite electromagnetic shielding film is obtained.
[0037] Tests showed that the film had an average electromagnetic shielding effectiveness of 46.23 dB in the X-band (8.2~12.4 GHz) and a tensile strength of 64.81 MPa.
[0038] Example 3 The present invention discloses a method for preparing a PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film, comprising the following steps: S1. 0.1 g of PBO fibers were added to a mixed acid solvent system consisting of TFA and MSA (TFA to MSA volume ratio of 1:1), and the mixture was magnetically stirred at room temperature for 72 h for acid-assisted dissociation. Subsequently, deionized water was added for solvent replacement, and residual acidic solvent was removed by vacuum filtration and washing with deionized water. Finally, the obtained PBO filter cake was redispersed in deionized water and homogenized to obtain a PBO nanofiber dispersion with a concentration of 1 mg / mL.
[0039] S2. Mix 0.1 g CNT, 0.25 g sodium dodecylbenzenesulfonate and 50 mL deionized water, and treat with ultrasound at 550 W for 1.5 h to obtain a CNT dispersion with a concentration of 2 mg / mL.
[0040] S3. Add 1 mmol Fe(NO3)3·9H2O and 1 mmol terephthalic acid to a mixed solvent consisting of 12.5 mL DMF, 1 mL deionized water, and 1 mL ethanol, and stir thoroughly until a homogeneous solution is formed. Then add 1 mL triethylamine, continue stirring, and transfer the resulting mixed solution to a reaction vessel. Perform a solvothermal reaction at 120 °C for 10 h. After the reaction is complete, collect the product, wash with deionized water and ethanol, and then dry at 70 °C for 16 h to obtain Fe-MOF powder.
[0041] S4. Mix 15 mL of PBO nanofiber dispersion and 20 mg of Fe-MOF and sonicate to obtain PBO / Fe-MOF mixture.
[0042] S5. Mix 15 mL of PBO nanofiber dispersion and 5 mL of CNT dispersion and ultrasonically disperse to obtain PBO / CNT mixture.
[0043] S6. Using a layer-by-layer assembly method, the PBO / Fe-MOF mixture obtained in S4 and the PBO / CNT mixture obtained in S5 are sequentially assembled and filtered to form a film. After hot pressing at 70℃ for 20 h, an asymmetric Janus structure PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film is obtained.
[0044] The film was tested and found to have an average electromagnetic shielding effectiveness of 46.73 dB in the X-band (8.2 ~ 12.4 GHz) and a tensile strength of 58.82 MPa.
[0045] Comparative Example 1 The preparation method of PBO nanofiber-based composite electromagnetic shielding film includes the following steps: S1. 0.2 g of PBO nanofibers were added to a mixed acid solvent system consisting of TFA and MSA (TFA to MSA volume ratio of 1.5:1), and the mixture was magnetically stirred at room temperature for 96 h for acid-assisted dissociation. Subsequently, deionized water was added for solvent replacement, and residual acidic solvent was removed by vacuum filtration and washing with deionized water. Finally, the obtained PBO filter cake was redispersed in deionized water, and after homogenization, a PBO nanofiber dispersion with a concentration of 1 mg / mL was obtained.
[0046] S2. Mix 0.2 g CNT, 0.5 g sodium dodecylbenzenesulfonate and 100 mL deionized water, and treat with ultrasound at 600 W for 1 h to obtain a CNT dispersion with a concentration of 2 mg / mL.
[0047] S3. Mix 30 mL of PBO nanofiber dispersion, 20 mg of Fe-MOF and 3 mL of CNT dispersion and ultrasonically disperse to obtain PBO / Fe-MOF / CNT mixture.
[0048] S4. The above PBO / Fe-MOF / CNT mixture was vacuum filtered and hot-pressed at 65°C for 18 h to obtain a PBO nanofiber-based composite electromagnetic shielding film.
[0049] Tests showed that the film had an average electromagnetic shielding effectiveness of 41.3 dB in the X-band (8.2~12.4 GHz) and a tensile strength of 31.59 MPa.
[0050] Comparative Example 2 The preparation method of PBO nanofiber-based composite electromagnetic shielding film includes the following steps: S1. 0.1 g of PBO fibers were added to a mixed acid solvent system consisting of TFA and MSA (TFA to MSA volume ratio of 1:1), and the mixture was magnetically stirred at room temperature for 72 h for acid-assisted dissociation. Subsequently, deionized water was added for solvent replacement, and residual acidic solvent was removed by vacuum filtration and washing with deionized water. Finally, the obtained PBO filter cake was redispersed in deionized water and homogenized to obtain a PBO nanofiber dispersion with a concentration of 1 mg / mL.
[0051] S2. Mix 0.1 g CNT, 0.25 g sodium dodecylbenzenesulfonate and 50 mL deionized water, and treat with ultrasound at 500 W for 2 h to obtain a CNT dispersion with a concentration of 2 mg / mL.
[0052] S3. Mix 30 mL of PBO dispersion, 20 mg of Fe-MOF and 5 mL of CNT dispersion and ultrasonically disperse to obtain PBO / Fe-MOF / CNT mixture.
[0053] S4. The above PBO / Fe-MOF / CNT mixture was vacuum filtered and hot-pressed at 70°C for 15 h to obtain a nano-PBO fiber-based composite electromagnetic shielding film.
[0054] Tests showed that the film had an average electromagnetic shielding effectiveness of 46.25 dB in the X-band (8.2~12.4 GHz) and a tensile strength of 39.3 MPa.
[0055] Example 4 like Figure 1a and Figure 1b As shown, the composite film prepared in Example 2 exhibits a brown and black appearance on its two sides, respectively, demonstrating a distinct bilayer functional structure. The PBO / Fe-MOF layer is uniformly brown, indicating that the Fe-MOF component was successfully incorporated into the PBO nanofiber network; the PBO / CNT layer is uniformly black, attributed to the introduction of CNTs. Figure 1c The composite film can be bent to a great extent without significant cracking, indicating that the constructed PBO nanofiber-based Janus composite film has good flexibility and structural stability.
[0056] Example 5 The asymmetric Janus-structured PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film prepared in Example 2 was used for performance testing. The morphology of the composite film was observed using scanning electron microscopy (SEM). The morphology of the upper and lower surfaces of the composite film is shown in the figure. Figures 2a-2d and Figures 3a-3d As shown, the PBO / Fe-MOF layer exhibits a dense fibrous network structure on its surface, with Fe-MOF nanoparticles uniformly loaded within the PBO fiber network. EDS elemental surface scanning results show that C, O, and Fe elements are uniformly distributed on the surface of the composite layer, indicating that the Fe-MOF nanoparticles are well dispersed in the PBO network. The PBO / CNT layer possesses a dense and continuous nanofiber network structure with no obvious defects on its surface. EDS elemental surface scanning results indicate that C, N, and O elements are uniformly distributed in the functional layer, demonstrating that CNTs have good dispersion in the PBO matrix and form a stable conductive functional layer. The cross-sectional SEM and EDS images of the composite film prepared in Example 2 are shown below. Figures 4a-4i As shown, the cross-section of the asymmetric Janus structure composite film exhibits a distinct bilayer structure with a continuous interface between the two functional layers. No obvious delamination, pores, or cracks were observed. High-magnification SEM images reveal that PBO nanofibers intertwine in the interfacial region, forming a continuous transition structure, which enhances the bonding stability between the two functional layers. EDS elemental surface scanning results show that C, N, O, and Fe elements exhibit characteristic distributions along the cross-sectional direction. Fe is mainly concentrated in the Fe-MOF functional layer region, while C, N, and O elements permeate the entire composite film, indicating that the PBO nanofiber network plays a connecting and supporting role between the two functional layers. Since both functional layers use PBO nanofibers as the matrix, the heterocyclic structures in the PBO molecular chain can generate interfacial interactions with CNTs, which helps improve the bonding stability of the heterogeneous interface.
[0057] Example 6 Figure 5 This is a diagram showing the overall electromagnetic shielding effectiveness of the composite film prepared in Example 1. Figure 6 This is a diagram showing the total electromagnetic shielding effectiveness of the composite film prepared in Example 2; Figure 7 This is a diagram showing the total electromagnetic shielding effectiveness of the composite film prepared in Example 3; Figure 8 This is a diagram showing the overall electromagnetic shielding effectiveness of the composite thin film prepared in Comparative Example 1. Figure 9 This is a diagram showing the overall electromagnetic shielding effectiveness of the composite film prepared in Comparative Example 2; Figure 10 This is a comparison chart of the absorption shielding effectiveness, reflection shielding effectiveness, and total shielding effectiveness of the composite films in the examples and comparative examples. Compared with Comparative Example 1, Example 2 exhibits higher electromagnetic shielding effectiveness (approximately 46 dB), while the tensile strength increases from 31.59 MPa to 64.81 MPa, indicating that a reasonable functional layer distribution can promote multiple losses of electromagnetic waves within the material and enhance structural stability. Similarly, under the same CNT content, Example 3 has similar electromagnetic shielding performance to Comparative Example 2, but the tensile strength increases from 39.3 MPa to 58.82 MPa, further demonstrating that the Janus structure can effectively improve the mechanical properties of the composite film while maintaining excellent electromagnetic shielding capabilities.
Claims
1. A PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film, characterized in that, It includes a PBO / Fe-MOF absorption loss layer and a PBO / CNT conductive loss layer. Both functional layers use PBO nanofibers as a common matrix and are constructed by layer-by-layer assembly to form a composite electromagnetic shielding film with an asymmetric Janus structure.
2. A method for preparing PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film, characterized in that, Specifically: Step 1: Prepare PBO nanofiber dispersion; Step 2, prepare CNT dispersion; Step 3, prepare Fe-MOF; Step 4: The PBO nanofiber dispersion and Fe-MOF are ultrasonically mixed to obtain a PBO / Fe-MOF mixture; Step 5: The PBO nanofiber dispersion and the CNT dispersion are ultrasonically mixed to obtain a PBO / CNT mixture; Step 6: Using a layer-by-layer assembly method, the PBO / Fe-MOF mixture and the PBO / CNT mixture are vacuum filtered to form a film and then hot-pressed to obtain a PBO nanofiber-based Fe-MOF / CNT composite electromagnetic shielding film.
3. The method for preparing the PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film as described in claim 2, characterized in that, In step 1, specifically: PBO nanofibers were added to a mixed acid solvent system consisting of trifluoroacetic acid and methanesulfonic acid, stirred, and acid-assisted dissociation was carried out for 24-96 hours to form a PBO nanofiber dispersion. Subsequently, deionized water was added for solvent replacement, and the PBO filter cake was redispersed and homogenized after vacuum filtration and washing with deionized water to obtain a PBO nanofiber dispersion with a concentration of 0.5-5 mg / mL.
4. The method for preparing the PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film as described in claim 2, characterized in that, Step 2 specifically involves: CNTs were mixed with sodium dodecylbenzenesulfonate and added to deionized water. The mixture was then subjected to ultrasonic treatment using an ultrasonic cell disruptor with an ultrasonic power of 300-600 W and an ultrasonic time of 1-2 h to obtain a CNT dispersion with a concentration of 1-5 mg / mL.
5. The method for preparing the PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film as described in claim 2, characterized in that, Step 3 specifically involves: Fe(NO3)3·9H2O and terephthalic acid ligands were added to a mixed solvent consisting of N,N-dimethylformamide, deionized water and ethanol, and stirred to form a homogeneous solution. Triethylamine was then added as a ligand deprotonating agent, and the mixture was stirred continuously before being transferred to a reaction vessel for a solvothermal reaction. After the reaction was completed, the precipitate was collected, washed with deionized water and ethanol, and finally dried to obtain Fe-MOF powder.
6. The method for preparing the PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film as described in claim 5, characterized in that, The molar ratio of Fe(NO3)3·9H2O to terephthalic acid ligand is 0.1~5:0.1~5; the solvothermal reaction temperature is 100~200℃, the solvothermal reaction time is 6~24h, the drying temperature is 50~70℃, and the drying time is 12~24h.
7. The method for preparing the PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film as described in claim 2, characterized in that, In step 5, the volume ratio of PBO nanofiber dispersion to CNT dispersion is 5~50:0.5~20.
8. The method for preparing the PBO nanofiber-based Fe-MOF / CNT electromagnetic shielding film as described in claim 2, characterized in that, In step 6, the hot pressing temperature is 50~80℃ and the hot pressing time is 15~30 h.